47. SAFETY AND EFFICIENCY OF THE HEART FAILURE MANAGEMENT PROGRAM AT FAMILY MEDICINE CLINICS (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to evaluate the safety and effectiveness of an integrated heart failure management program at the family medicine (primary care) level by comparing clinical and paraclinical indicators of patients before and after participating in the program.Material and methods: A prospective descriptive study was conducted on 108 patients with stable chronic heart failure receiving care at Family Medicine Clinics of District 2 and District 4 Hospitals, Ho Chi Minh City.Results: Participants' socio-demographic characteristics and comorbidity profiles were comparable to those reported in previous studies. After intervention, clinical symptoms, left ventricular ejection fraction, and exercise capacity significantly improved. Conclusion: These findings demonstrated that the integrated heart failure management
Keywords: Family medicine; primary care; heart failure management; 6-minute walk test